Diyarbekir Şer'iyye Sicilleri (Diyarbakır Diyarbakır Diyarbakır Diyarbakır Diyarbakır Diyarbakır)
10 c. (lxiii, 571 s. ; lix, 636 s. ; lxxii, 930 s. ; lx, 948 s. ; lviii, 890 s. ; lii, 832 s. ; lxii, 668 s. ; l, 668 s. ; liv, 716 s. ; lii, 780 s.)